Austerity policy and child health in European countries: a systematic literature review - Luis Rajmil; Anders Hjern; Nick Spencer; David Taylor-Robinson; Geir Gunnlaugsson; Hein Raat (BMC, 2020)
Abstract Background To analyse the impact of austerity measures taken by European governments as a response to the 2008 economic and financial crisis on social determinants on child health (SDCH), and child health outcomes (CHO). Methods A systematic literature review was carried out in Medline (Ovid), Embase, Web of Science, PsycInfo, and Sociological abstracts in the last 5 years from European countries. Studies aimed at analysing the Great Recession, governments' responses to the crisis, and its impact on SDCH were included. A narrative synthesis of the results was carried out. The risk of bias was assessed using the STROBE and EPICURE tools. Results Fourteen studies were included, most of them with a low to intermediate risk of bias (average score 72.1%). Government responses to the crisis varied, although there was general agreement that Greece, Spain, Ireland and the United Kingdom applied higher levels of austerity. High austerity periods, compared to pre-austerity periods were associated with increased material deprivation, child poverty rates, and low birth weight. Increasing child poverty subsequent to austerity measures was associated with deterioration of child health. High austerity was also related to poorer access and quality of services provided to disabled children. An annual reduction of 1% on public health expenditure was associated to 0.5% reduction on Measles-Mumps-Rubella vaccination coverage in Italy. Conclusions Countries that applied high level of austerity showed worse trends on SDCH and CHO, demonstrating the importance that economic policy may have for equity in child health and development. European governments must act urgently and reverse these austerity policy measures that are detrimental to family benefits and child protection.